Evaluating the Fit of the Parent Company With Businesses to Develop Corporate Strategy (Case Study: Ikco Employees Cooperative) (Malaysian Management Journal, 2014)
Deciding business portfolio, investment approach, and parenting management style need to understand how the fit of the parent company and its business, and the degree of potential of value creation by the parent. So, it is important to measure the fitness. This research which analysed factors affecting the characteristics of business and the parent company, offers a model to measure fitness. The proposed model has been implemented in a holding company and its results can be used to develop corporate strategy.